Hubungan antara Dukungan Sosial dengan Tingkat Stress pada Remaja di Panti Asuhan Mambaul Ulum Sumbersari - Nadhir, Muhammad Ulin; Faqih, Moh. Mahfudz; Nasihah, Fazdilatun (Sociocouns: Journal of Islamic Guidance and Counseling, 2026)
The study aims to determine the level of social support for adolescents at the Mambaul Ulum Sumbersari Orphanage, to determine the level of stress in adolescents at the Mambaul Ulum Sumbersari Orphanage and to determine the correlation between social support and stress levels in adolescents at the Mambaul Ulum Sumbersari orphanage. The study uses a quantitative method with a correlation approach, with a population of 25 adolancents and asaturated sample of all 25 adolescents at the Mambaul Ulum Sumbersari orphanage. The data in this study used a scale of social support and stress level. The results of the study using product momet analysis showed a sig. velue of 0.001 < 0.05 thus, there is a significant negative relationship between social support and stress levels in adolescents at the Mambaul Ulum Sumbersari Orphanage. From the existing results, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) proposed by the researcher which states “social support is negatively correlated with stress levels in adolescents at the Mambaul Ulum Sumbersari Orphanage” is accepted.  This study concluded that 1) the level of social support received by adolescents at the Mambaul Ulum Sumbersari orphanage is classified as moderate 2) the level of stress experienced by adolescents at the Mambaul Ulum Sumbersari orphanage is included in the moderate category 3) social support is negatively correlated significantly wwith the levelof stress in adolescents at the Mambaul Ulum Sumbersari orphanage. In other words, the higher the sosial support received by adolescents, the lower the level of stress experienced. Conversely, the lower the social support, the higher the level of stress.